1979
DOI: 10.1037/0022-0167.26.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Counselor trainee anxiety during counseling.

Abstract: Physiological and subjective anxiety measures were assessed to determine if counselor trainees experienced greater anxiety levels during a counseling interview than during a conversation. Twenty-eight counselor trainee volunteers from a graduate level practicum course participated in 10-minute conversation and counseling sessions. Anxiety was assessed by self-report, skin conductance, and heart rate measures. Results indicated that on two of three indicants of anxiety, trainees were more anxious during counsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

1979
1979
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 2 publications
1
16
0
3
Order By: Relevance
“…Thus, these instruments appear to have high face validity when compared to instruments providing a general assessment of state anxiety. Further evidence of validity is found in the nonsignificant low positive correlations between scores on these instruments and physiological data , 1979Bowman, Roberts, & Giesen, 1978). These results are consistent with literature that reports that although physiological and verbal/cognitive dimensions of anxiety are related to some degree, they show a marked degree of independence from one another (Mathews, 1971).…”
Section: Apparatus and Instrumentssupporting
confidence: 91%
“…Thus, these instruments appear to have high face validity when compared to instruments providing a general assessment of state anxiety. Further evidence of validity is found in the nonsignificant low positive correlations between scores on these instruments and physiological data , 1979Bowman, Roberts, & Giesen, 1978). These results are consistent with literature that reports that although physiological and verbal/cognitive dimensions of anxiety are related to some degree, they show a marked degree of independence from one another (Mathews, 1971).…”
Section: Apparatus and Instrumentssupporting
confidence: 91%
“…State anxiety was not significantly different over time. These results do not support conclusions that counseling sessions cause anxiety for CITs Bowman & Roberts, 1979a;Bowman & Roberts, 1979b;Diblin, 1969;Kaplan, 1983;Mooney & Carlson, 1976), either anticipatory anxiety or pervasive anxiety (Bernard & Goodyear, 1992;Ronnestad & Skovholt, 1993;Skovholt & Ronnestad, 1992).…”
Section: Discussionmentioning
confidence: 75%
“…Some empirical studies about novice CIT anxiety have supported these perspectives including those by Bowman, Roberts and Giesen (1978) and 1979a;1979b) who found that CITs were more anxious during counseling than during reading or noncounseling conversations. Olk and Friedlander (1992), in a qualitative study, found that novice CITs were more anxious about evaluation and discussing personal concerns and doubts, and more dependent upon faculty supervisor evaluations than doctoral CITs.…”
mentioning
confidence: 94%
“…The finding from Barbee, Scherer, and Combs (2003) of an inverse relationship between self-efficacy and anxiety is an interesting one that has received empirical support from other researchers (Bowman & Roberts, 1979;Friedlander, Keller, Peca-Baker, & Olk, 1986). According to Bandura, selfefficacy relates to one's ability to deal with stressful or anxiety-provoking situations; with increasing self-efficacy, one's belief that he or she can deal with anxiety/arousal also increases (Bandura, 1993).…”
Section: Self-efficacy and Affectmentioning
confidence: 74%